Synergistic effects of crystal phases and mixed valences in La-Sr-Ce-Fe-O mixed oxidic/perovskitic solids on their catalytic activity for the NO+CO reaction - Belessi, Vassiliki; Bakas, Thomas V.; Costa, Costas; Efstathiou, A. M.; Pomonis, Phillippos J. (My University, 2000)
Mixed oxidic and perovskite-type materials based on the La, Sr, Ce and Fe elements were prepared using a mixture of nitrates salts and heating at 1000°C. Three groups of solids were synthesized: (i) La1−yCeyFeO3 (y=0.2, 0.3, 0.5), (ii) La1−xSrxFeO3 (x=0.2, 0.3, 0.5) and (iii) La1−x−ySrxCeyFeO3 (x/y=0.05/0.15, 0.15/0.05, 0.1/0.2, 0.2/0.1, 0.2/0.3 and 0.3/0.2). The structure of the solids was examined by XRD and the main crystal phases determined were LaFeO3, α-Fe2O3 and CeO2 in group (i), LaFeO3 and SrFeO3−x in group (ii), and LaFeO3, α-Fe2O3, SrFeO3−x and CeO2 in group (iii), while traces of La(OH)3 and SrFe12O19 were also detected. The precise determination of the percentage amount of the iron-containing crystal phases in each solid composition was determined by Mössbauer spectroscopy at 20 K. The ceramic materials had low surface areas and were tested for their catalytic activity for the NO+CO reaction in a flow reactor in the range of 280–560°C. Conversions as high as 90% were achieved at 550°C at a GHSV=54 000 h−1. The reaction rate of NO conversion is favored by the increased amount of CeO2 in groups (i) and (iii) of solids that contain cerium. In the case of solids without CeO2 (group ii), the NO conversion is favored by the existence of SrFeO3−x phase at low temperatures (280–440°C), while it decreases at high temperatures (440–560°C). The double substituted solids La1−x−ySrxCeyFeO3 with x+y>0.3 and y>x were found to be the best catalysts for the NO+CO reaction as compared to the single substituted mixed oxides. Temperature programmed desorption (TPD) studies of NO and CO2 support the view that a synergistic effect takes place between the two phases of CeO2 and SrFeO3−x, whose co-existence results in the maximum enhancement of activity, via alternative oxidation–reduction cycles in the two phases.
Keywords: Carbon monoxide; Catalytic reduction of NO; CO2 TPD; Mossbauer; Nitrogen monoxide; NO TPD; Perovskite